2018
DOI: 10.1371/journal.pone.0194446
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous assessment of glycosylated hemoglobin, fasting plasma glucose and oral glucose tolerance test does not improve the detection of type 2 diabetes mellitus in Colombian adults

Abstract: IntroductionGuidelines recommend early detection of type 2 diabetes mellitus (DM2). The objective of the present study was to evaluate the capacity to identify DM2 in subjects that were screened for DM2 simultaneously with all three of the tests recommended—fasting plasma glucose (FPG), glycosylated hemoglobin (HbA1c) and a 2-hour post 75-g oral glucose tolerance test (OGTT).Methods and resultsThe present analysis of an anonymous database of 1113 adults from a reference clinical laboratory in Bucaramanga, Colo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Lopez-Lopez et al [37] investigated the effect of simultaneously measuring HbA1c, fasting glucose values and a 2-hour glucose values in detecting new T2DM. They concluded that measuring both fasting and 2-hour glucose values showed the highest proportion of patients with new T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Lopez-Lopez et al [37] investigated the effect of simultaneously measuring HbA1c, fasting glucose values and a 2-hour glucose values in detecting new T2DM. They concluded that measuring both fasting and 2-hour glucose values showed the highest proportion of patients with new T2DM.…”
Section: Discussionmentioning
confidence: 99%